(Co-)combustion of additives, water hyacinth and sewage sludge: Thermogravimetric, kinetic, gas and thermodynamic modeling analyses. (November 2018) - Liu, Jingyong; Huang, Limao; Sun, Guang; Chen, Jiacong; Zhuang, Shengwei; Chang, Kenlin; Xie, Wuming; Kuo, Jiahong; He, Yao; Sun, Shuiyu; Buyukada, Musa; Evrendilek, Fatih
Highlights: (Co-)combustion of sewage sludge with five additives was quantified. K2 CO3 and MgCO3 decreased E m value of sewage sludge. Water hyacinth and K2 CO3 increased CO2, NO2, SO2 but reduced HCN and NH3 emissions. Abstract: Additives and biomass were co-combusted with sewage sludge (SS) to promote SS incineration treatment and energy generation. (Co-)combustion characteristics of sewage sludge (SS), water hyacinth (WH), and 5% five additives (K2 CO3, Na2 CO3, Mg2 CO3, MgO and Al2 O3 ) were quantified and compared using thermogravimetric-mass spectrometric (TG-MS) and numerical analyses. The combustion performance of SS declined slightly with the additives which was demonstrated by the 0.03-to-0.25-fold decreases in comprehensive combustibility index ( CCI ). The co-combustion performed well given the 0.31-fold increase in CCI . Kinetic parameters were estimated using the Ozawa-Flynn-Wall (OFW) and Kissinger-Akahira-Sunose (KAS) methods. Apparent activation energy estimates by OFW and KAS were consistent. The addition of K2 CO3 and MgCO3 decreased the weighted average activation energy of SS. Adding K2 CO3 to the blend reduced CO2, NO2, SO2, HCN and NH3 emissions. CO2, NO2 and SO2 emissions were higher from WH than SS. Adding WH or K2 CO3 to SS increased CO2, NO2 and SO2 but HCN and NH3 emissions. Based on both catalytic effects and evolved gases, K2 CO3 was potentially an optimal option for the catalytic combustion among the tested additives.